Study on macro-and mesoscopic damage characteristics of fractured sandstoneunder cyclic loading and unloading with variable upper limit - Guangjian LIU; Hao ZHOU; Zonglong MU; Kangyu WANG; Weiqi QIU; Xi CHEN; Zhicheng WANG (Meitan kexue jishu)
Abstract: In order to study the macro and micro damage characteristics of fractured rock mass under cyclic load, cyclic loading and unloading tests with variable upper limit were carried out to analyze the mechanical properties and macro failure characteristics of the samples. Based on the results of XRD analysis, a UDEC numerical model of fractured sandstone is constructed to analyze the microscopic damage law of the model and reveal its mechanism. The results show that: loading and unloading can strengthen the deformation resistance of the samples with small cracks, and on the contrary increase the failure velocity of the samples with large cracks; With the increase of the prefabricated fracture length, the macroscopic failure characteristics of the sample changed from tensile shear failure to shear failure, and the irreversibility of the damage gradually increased. The damage evolution process of the sample under loading and unloading can be divided into four stages: “elasticity-strengthening-fatigue-failure”. No damage occurs in the elastic stage model, while an effective resistance structure is formed in the strengthening stage model. Cumulative damage increases significantly in the fatigue stage, and tensile cracks expand during unloading. During the loading stage, cracks expand and connect with each other, the contact point pole of the block between adjacent shear microcracks is destroyed, and the connection between the blocks fails. During the unloading process, the stress drop model is relaxed, and the failed connection between the blocks opens up at this time, leading to the initiation of tension cracks between the shear microcracks, and accelerating the instability and failure of the model. The research results reveal the macro and micro damage characteristics of fractured sandstone under variable upper limit cyclic loading and unloading, and provide a reference for scientific evaluation of engineering stability.